Tumbuhan Lotus sebagai Inspirasi Pembuatan Motif Digital Printing Outerwear Zero Waste - Nabilah, Fiqrotun; Suhartini, Ratna (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
The research objective was to find out the finished product of making the outer using the zero waste concept with decorative motifs inspired by the lotus applied to the fabric using digital printing techniques. Pattern making using the zero waste concept was chosen because, the increasing production of ready-to-wear clothes makes the industry produce more textile which can have a negative impact on the environment due to excessive waste disposal. Lotus as a motif on the outer has the local name seroja classified in the family (Nelumboceae), is a plant that lives in water and originates from India, however, the existence of the lotus plant grows almost in Asian countries such as China, Thailand and others. The lotus is often referred to as a waterlily even though it has differences in shape and how it grows, a lotus that grows with flowers rising from the bottom of the water does not float above the water like a lotus. As time goes on, making decorative motifs uses more modern techniques or are called with digital printing techniques. Motifs from the lotus inspiration are applied to cloth using digital printing techniques to speed up the process of embodiment of motifs on cloth.